2015
DOI: 10.3389/fmicb.2015.01104
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and microbial factors influencing methane and nitrous oxide fluxes in Mediterranean cork oak woodlands: trees make a difference

Abstract: Cork oak woodlands (montado) are agroforestry systems distributed all over the Mediterranean basin with a very important social, economic and ecological value. A generalized cork oak decline has been occurring in the last decades jeopardizing its future sustainability. It is unknown how loss of tree cover affects microbial processes that are consuming greenhouse gases in the montado ecosystem. The study was conducted under two different conditions in the natural understory of a cork oak woodland in center Port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 73 publications
(80 reference statements)
1
9
0
Order By: Relevance
“…Considering the entire un-stratified plot, spatial variability (evaluated as coefficient of variation CV) of the standardized CO2 and CH4 fluxes and non-standardized N2O flux was highest for N2O and similar for CO2 and CH4 (Tab. 1) and agrees well with data from literature [14,49]. Since the vegetation strata could explain some of the spatial variability of the soil gas fluxes at our site, our stratification approach reduced the CV for CH4 substantially, from 38% to 24% (Tab.…”
Section: Spatial Variability Of Soil Gas Fluxessupporting
confidence: 90%
See 2 more Smart Citations
“…Considering the entire un-stratified plot, spatial variability (evaluated as coefficient of variation CV) of the standardized CO2 and CH4 fluxes and non-standardized N2O flux was highest for N2O and similar for CO2 and CH4 (Tab. 1) and agrees well with data from literature [14,49]. Since the vegetation strata could explain some of the spatial variability of the soil gas fluxes at our site, our stratification approach reduced the CV for CH4 substantially, from 38% to 24% (Tab.…”
Section: Spatial Variability Of Soil Gas Fluxessupporting
confidence: 90%
“…Few studies though could stratify or explain spatial variability of GHG fluxes on the plot scale. Shvaleva et al [49] showed that tree cover had an effect on net N 2 O fluxes and that CH 4 fluxes were affected by soil organic carbon content. Darenova et al [14] identified litter thickness and local soil moisture as important factors affecting CO 2 fluxes on the plots scale within a forest and grassland.…”
Section: Spatial Variability Of Soil Gas Fluxesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, montado systems have a higher density and richness of ectomycorrhizal (ECM) fungal communities than regions with denser tree and shrub cover, due to lower competition; this can increase the resilience of the managed system due to improved nutrient acquisition, drought tolerance and pathogen resistance (Azul et al, 2010). The montado landscape has also been shown to have other effects such as lowering land surface temperature (Godinho et al, 2016) or affecting soil microbiology (Shvaleva et al, 2015) and soil fauna (Martins da Silva et al, 2015).…”
Section: Rewilding In Sloveniamentioning
confidence: 99%
“…Upland forest soils, even when well-aerated, can also act as a sink for atmospheric N 2 O. Periodic N 2 O uptake has been observed during dry periods in temperate Norway spruce forests (Bowden et al 1991;Klemedtsson et al 1997;Butterbach-Bahl et al 1998;Goldberg and Gebauer 2009), during spring and autumn in temperate Red pine (Bowden et al 1990) and Scots pine forests (Butterbach-Bahl et al 2002) and boreal pine dominated forest (Machakova et al 2019), in deciduous forests (Dong et al 1998;Goossens et al 2001), as well as in Mediterranean pine (Rosenkranz et al 2006) and oak forests (Shvaleva et al 2015). According to the best of our knowledge, data on N 2 O uptake from boreal spruce forests, an important coniferous forest type in the boreal region, is currently lacking.…”
Section: Introductionmentioning
confidence: 99%